2020
DOI: 10.1088/2053-1591/ab67fb
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical performance of ropelike LiNi0.8Co0.15Al0.05O2 fiber with nano-building blocks

Abstract: A ropelike LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA) fiber with superior rate capability and cycling stability was successfully synthesized via electrospinning and sintering as a cathode material for Li-ion batteries. The NCA fiber that exhibited excellent electrochemical performance as a cathode for Li-ion batteries was stacked and assembled from numerous nanoparticles. The NCA fiber delivered a high reversible capacity of 206.4 mAh g −1 at 0.1 C, and maintained 75% capacity retention after 100 cycles at 1 C. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Zhang et al successfully synthesized a unique rope-like NCA fiber through electrospinning and sintering, which effectively shortened the Li-ion diffusion path and improved the Li-ion diffusion coefficient. [38] In addition, the fibrous structure was also beneficial to increase the contact area between electrolyte and active particles and reduce the aggregation of active particles. The results showed that the NCA fiber electrode exhibited excellent electrochemical performances, with a high discharge capacity of 206.4 mA h g −1 at 0.1 C and a capacity retention of 81.5% after 100 cycles at 0.5 C. In addition, it also maintained a good fiber structure during the cycle.…”
Section: Layeredmentioning
confidence: 99%
“…Zhang et al successfully synthesized a unique rope-like NCA fiber through electrospinning and sintering, which effectively shortened the Li-ion diffusion path and improved the Li-ion diffusion coefficient. [38] In addition, the fibrous structure was also beneficial to increase the contact area between electrolyte and active particles and reduce the aggregation of active particles. The results showed that the NCA fiber electrode exhibited excellent electrochemical performances, with a high discharge capacity of 206.4 mA h g −1 at 0.1 C and a capacity retention of 81.5% after 100 cycles at 0.5 C. In addition, it also maintained a good fiber structure during the cycle.…”
Section: Layeredmentioning
confidence: 99%
“…Ropelike NCA fiber was prepared via electrospinning and sintering. As a cathode, it delivered a capacity of 206.4 mAh g −1 at 0.1 C, and maintained 75% capacity retention after 100 cycles at 1 C [34]. A green and low-cost synthesis of NCA was also proposed, by using C 4 H 4 O 6 KNa•4H 2 O as a chelating agent to prepare Ni 0.80 Co 0.15 Al 0.05 (OH) 2 used as the precursor obtained through a coprecipitation method using potassium sodium tartrate [35].…”
Section: Synthesismentioning
confidence: 99%
“…The same author has carried out another study where a capacity of 160.2 mAh g −1 at 1C-rate for LiNi 0.8 Co 0.15 Al 0.05 O 2 cathode is reported on rope-like morphology synthesized through the electrospinning (ES) process. 14 However, the high Ni-based NMC cathode prepared by ES showed poor capacity retention of 74.9% after 100 cycles at 1C-rate. While there are few studies that address the methods to improve the electrochemical properties of cathode materials, such as Li-rich layered oxide, studies on nanofibrous Ni-rich layered oxides processed by the ES technique are scarce.…”
Section: Introductionmentioning
confidence: 98%
“…An initial discharge capacity of 191.2 mAh g −1 and capacity retention of 84% after 100 cycles are reported for the sample calcined at 750°C. The same author has carried out another study where a capacity of 160.2 mAh g −1 at 1C‐rate for LiNi 0.8 Co 0.15 Al 0.05 O 2 cathode is reported on rope‐like morphology synthesized through the electrospinning (ES) process 14 . However, the high Ni‐based NMC cathode prepared by ES showed poor capacity retention of 74.9% after 100 cycles at 1C‐rate.…”
Section: Introductionmentioning
confidence: 99%